Cover Feature: Manipulating the Optical Properties of Carbon Dots by Fine‐Tuning their Structural Features (ChemSusChem 19/2019). Issue 19 (26th September 2019) - Luo, Hui; Papaioannou, Nikolaos; Salvadori, Enrico; Roessler, Maxie M.; Ploenes, Gereon; van Eck, Ernst R. H.; Tanase, Liviu C.; Feng, Jingyu; Sun, Yiwei; Yang, Yan; Danaie, Mohsen; Belen Jorge, Ana; et al.
Abstract : The Cover Feature shows emission in oxidized and reduced carbon dots. The interaction between oxidized carbon dots (upper left) with UV light results in green emission whereas in the case of reduced carbon dots (lower right) mainly photo‐assisted thermal relaxation is detected. Such different phenomena occurring within the exited states of hydrothermal carbon dots are controlled by different structural features, with oxidized carbon dots containing more oxygen functionalities and reduced carbon dots having mainly conjugated domains. More information can be found in the Full Paper by H. Luo et al. onpage 4432 in Issue 19, 2019 (DOI:10.1002/cssc.201901795 ).